Editorial (English) - Mota, Maurício (REVISTA QUAESTIO IURIS, 2016)
Editorial for vol. 08-4 (2015) - Special Number DOI: 10.12957/rqi.2015.20926 The Journal Quaestio Iuris, ranked by MEC / CAPES as Qualis A2, Law, in this volume 08, number 04, 2015, Special Number, has the great pleasure to inform all readers and friends that, from this number of Quaestio Iuris, we will have quarterly publication, with numbers in February, May, August and November.